Insurance as an agricultural disaster risk management tool: evidence and lessons learned from South Asia - Amarnath, Giriraj; Ghosh, Surajit; Alahacoon, Niranga; Ravan, Shirish Kumar; Taneja, P.K.; Dave, Nisarg; Srivastava, Sanjay K. (CGIAR Research Program on Water, Land and Ecosystems, 2019)
Pilot projects in India and Bangladesh demonstrate that index-based weather insurance products, developed using satellite technology, can reduce the financial risks to smallholder farmers from floods and droughts. Scaling up such schemes has the potential to meet the needs of very vulnerable groups, especially women and assist governments in meeting global development goals.